Elaboration of management mechanism of innovative development of coal industry in Ukraine - Лизунова, Олена Миколаївна (Technology audit and production reserves, 2015)
Theoretical and methodological approaches to the management of innovative development of coal enterprises in Ukraine have been considered in the article, a common approach to the definition of «innovative development of the enterprise» were analyzed. Results of the analysis helped to identify that most authors give a definition of a position evaluation is only one aspect, it prompted the author to summarize the existing approaches and give his own definition of innovative development of coal-mining enterprise that takes into account the specifics of the industry. Analysis of problems of innovative development of national coal industry was conducted. Based on this analysis the organizational and economic mechanism of innovative development of the Ukrainian coal industry is proposed. This mechanism involves the financing, material and personnel support in the area of production, work organization, marketing services and other. Implementation of innovative mechanisms for development of the coal industry will help achieve a balance of income and expenditure, improve productivity, competitiveness of coal production in the domestic and international coal markets, and increase comfort and create a safe working environment.